2017
DOI: 10.5901/jesr.2017.v7n2p103
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Level of Junior Secondary School Students′ Use of Listening Comprehension Strategies in Oredo Local Government Area of Edo State

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Those below 15 years old are likely to still have the luxury of time to engage in violent video since they are only writing school-based examinations. Unlikely Private Secondary School Students who are adequately monitored and taught Public Secondary School Students may not likely be restricted or strictly engaged, promoting students' exposure to various videos (Omorogbe & Iguodala, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those below 15 years old are likely to still have the luxury of time to engage in violent video since they are only writing school-based examinations. Unlikely Private Secondary School Students who are adequately monitored and taught Public Secondary School Students may not likely be restricted or strictly engaged, promoting students' exposure to various videos (Omorogbe & Iguodala, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors predispose public secondary school students to video exposure, especially violent videos, such as accessibility to video centers and peer influence. A previous study on attitude and motivation for social networks among secondary school students in Oredo Local Government Area of Edo State found that male respondents engaged more on social networks while younger students were motivated to engage on social networks owing to loose schedules (Omorogbe & Iguodala, 2018).…”
Section: Introductionmentioning
confidence: 97%